1983
DOI: 10.1016/0304-3959(83)90129-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of postoperative analgesic use with adults and children following cardiac surgery

Abstract: The postoperative prescription and administration of analgesics following cardiac surgery for 50 children were compared with those of 50 adults. Six children were the only patients in the sample who were prescribed no postoperative analgesics. Overall, children were prescribed significantly fewer potent narcotics. The administration data revealed even more pronounced group differences. During the observation period, children received 30% of all analgesic administrations while adults received 70%. Some possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1
6

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(90 citation statements)
references
References 13 publications
4
79
1
6
Order By: Relevance
“…These same extent as adults, and that children often beliefs have been proven wrong (7)(8)(9). Other experienced postoperative pain (1)(2)(3)(4)(5)(6). The reasons for misconceptions are, that it is unsafe to administer the undertreatment of pain in children were partly due opioids to children, and that children often suffer to the persistence of old myths such as 'small infants respiratory depression following administration of have an immature nervous system and are unable to morphine.…”
Section: Introductionmentioning
confidence: 94%
“…These same extent as adults, and that children often beliefs have been proven wrong (7)(8)(9). Other experienced postoperative pain (1)(2)(3)(4)(5)(6). The reasons for misconceptions are, that it is unsafe to administer the undertreatment of pain in children were partly due opioids to children, and that children often suffer to the persistence of old myths such as 'small infants respiratory depression following administration of have an immature nervous system and are unable to morphine.…”
Section: Introductionmentioning
confidence: 94%
“…One child received two aspirin tablets following spinal fusion, and two with 65-70% second and third degree burns received one aspirin and one acetaminophen tablet each. Beyer et al, 8 comparing 50 children with 50 adults undergoing open heart surgery, showed that the adults received more than twice as many doses of analgesics as the children. Similarly, Schecter et al 9 matched children and adults undergoing inguinal herniorrhaphy or appendectomy or sustaining fractured femurs or second degree burns and, again, the adults received twice as many doses of narcotics per day as the children.…”
Section: Mdtaboliques Aux Stimulation S Nociceptives Comme Chez Les mentioning
confidence: 99%
“…Primero, los estudios que mostraron que el dolor infantil estaba claramente desatendido en los hospitales. Efectivamente, entre finales de los años 70 y 80 del siglo pasado se publican los resultados de diversos trabajos que descubren y plantean abiertamente la nula atención al control del dolor infantil en los hospitales (12)(13)(14), provocando un intenso debate que fue más allá del ámbito profesional y de las sociedades científicas (11). Segundo, los estudios de Kanwaljeet S.…”
Section: Psicología Y Dolor Crónico (Infantil)unclassified